Mitigate the cytokine storm due to the severe COVID-19: A computational investigation of possible allosteric inhibitory actions on IL-6R and IL-1R using selected phytochemicals - Rajapaksha, Harindu; Perera, Bingun Tharusha; Meepage, Jeewani; Perera, Ruwan Tharanga; Dissanayake, Chithramala (European Journal of Chemistry, 2020)
The novel corona virus 2019 (COVID 19) is growing at an increasing rate with high mortality. Meanwhile, the cytokine storm is the most dangerous and potentially life-threatening event related to COVID 19. Phyto-compounds found in existing Ayurveda drugs have the ability to inhibit the Interleukin 6 (IL-6R) and Interleukin 1 (IL-1R) receptors. IL-6R and IL-1R receptors involve in cytokine storm and recognition of phytochemicals with proven safety profiles could open a pathway to the development of the most effective drugs against cytokine storm. In this study, we intend to perform an in silico investigation of effective phyto compounds, which can be isolated from selected medicinal herbs to avoid cytokine storm, inhibiting the IL-6 and IL-1 receptor binding process. An extensive literature survey followed by virtual screening was carried out to identify phytochemicals with potential anti-hyper-inflammatory action. Flexible docking was conducted for validated models of IL-1R and IL-6R-α with the most promising phytochemicals at possible allosteric sites using AutoDock Vina. Molecular dynamics (MD) studies were conducted for selected protein-ligand complexes using LARMD server and conformational changes were evaluated. According to the results, taepeenin J had Gibbs energy (ΔG) of -10.85 kcal/mol towards IL-1R but had limited oral bioavailability. MD analysis revealed that taepeenin J can cause significant conformational movements in IL-1R. Nortaepeenin B showed a ΔG of -8.5 kcal/mol towards IL-6R-α with an excellent oral bioavailability. MD analysis predicted that it can cause significant conformational movements in IL-6R-α. Hence, the evaluated phytochemicals are potential candidates for further in vitro studies for the development of medicine against cytokine storm on behalf of SARS-COV-2 infected patients.